The Cerita Kita Website: Enhancing Elementary Students’ Multiliteracy and Literary Appreciation through a Local Wisdom-Based Ecocriticism Approach - Mellyaning Khoiriya, Rika; Mudiono, Alif; Yuriananta, Renda; Kurnia, Vika Cahya; Faiza, Afidatun; Azizah, Maulidatil (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study developed the "Cerita Kita" website, integrating ecocriticism and local wisdom to enhance elementary students' multiliteracy and literary appreciation. Using design-based research with the ADDIE framework, the prototype's validity was measured through expert validation (CVI=0.89-0.91), practicality via implementation success rate (88%) and System Usability Scale (SUS=81.4), and effectiveness through stratified ecocriticism assessments and reflective journals. The study involved 84 fourth-graders in urban (n=33) and rural (n=51) Malang, Indonesia. Quantitative data analysis employed descriptive statistics and paired t-tests, showing significant multiliteracy gains, particularly in ecological awareness (rural: 78.6±18.3; urban: 56.4±21.7; p<0.01). Qualitative thematic analysis revealed that rural students' cultural connections drove their 39.2% superiority in environmental applications. The Coban Rondo legend proved most effective (87% ecological interpretation accuracy). Results demonstrate that cultural anchoring—not technological sophistication—is pivotal for digital multiliteracy, offering a sustainable model for Global South educational contexts that prioritizes cultural narratives over complex technology to achieve SDG 4.7 goals.